A note on a seed sterile nutmeg from the secondary center of domestication - Rema, B Sasikumar, K V Saji, J (Journal of Spices and Aromatic Crops, 2017)
A unique nutmeg accession having normal fruit, but with rudimentary, sterile seed and finely packed mace having a human brain like appearance was collected from a farmer’s garden from the secondary center of domestication of the crop and characterized. Seed (female) sterility in a dioecious or emerging monoecious plant like nutmeg is hitherto not recorded and is a novelty. This unique accession is conserved at the germplasm conservatory of tree spices at the ICAR-Indian Institute of Spices Research, Kozhikode, Kerala.